LAMBANGAN MENYALA: DESA TANI KREATIF DENGAN UMKM DAN KARYA DAUR ULANG - Sumiati, Sumiati; Mujanah, Siti (Semeru: Jurnal Pengabdian Kepada Masyarakat, 2025)
Lambangan Village has great potential in the development of innovative villages based on MSMEs, creative economy, and recycling. This article aims to explore community service outcomes that integrate local potential with digital technology and community empowerment. The method used is descriptive qualitative research with a participatory approach, through interviews, observations, and FGDs. The results show a significant increase in MSME digital skills, citizen participation, and the emergence of village icons based on recycled works. This research contributes to the development of a sustainable village model based on local assets. The findings also show the importance of cross-sector collaboration in building a creative village ecosystem. Further research is recommended to expand the scope of the area and use the triangulative method.